FINANCIAL RATIO ANALYSIS TO PREDICT A FINANCIAL DISTRESS (A Case Study in Manufactur Companies at Indonesia Stock Exchange) - Hermawan, Ade (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to determine the effect of financial ratios to predict financial distress in the company. Financial ratios in this research are leverage ratio indicator, liquidity ratio, activity ratio, and profitability ratio. The population in this study are all companies listed on the Indonesia Stock Exchange and publish the financial statements from 2014 to 2016. Using purposive sampling method, the sample obtained was 132 company and obtained 396 observation data. Criteria of financial distress in this study was measured by using earning per share, while statistical analysis used in this study was logistic regression. The results showed that the ratio of leverage (debt ratio) and liquidity ratio (current ratio) had no significant value to predict financial distress in the company, while the ratio of total asset turnover and profitability financial ratios had significant value to predict financial difficulties in the company.Keywords: financial difficulties, financial ratios, earnings per share.